Development and Assessment of a Brazilian Pilot Massive Open Online Course in Planetary Health Education: An Innovative Model for Primary Care Professionals and Community Training - Floss, Mayara; Vieira Ilgenfritz, Carlos Augusto; Rodrigues, Ylana Elias; Cláudia Dilda, Anna; Borngräber Corrêa, Ana Paula; Azevedo Conte de Melo, Diego; Falceto Barros, Enrique; Faerron Guzmán, Carlos Alberto; Devlin, Erin; Saldiva, Paulo Hilário Nascimento; Khoo, Su-Ming; Gonçalves, Marcelo Rodrigues; et al. (Frontiers in Public Health, 2021)
Introduction: Planetary health (PH) has emerged as a leading field for raising awareness, debating, and finding solutions for the health impacts of human-caused disruptions to Earth's natural systems. PH education addresses essential questions of how humanity inhabits Earth, and how humans affect, and are affected by, natural systems. A pilot massive open online course (MOOC) in PH was created in Brazil in 2020. This MOOC capitalized on the global online pivot, to make the course accessible to a broader audience. This study describes the process of course creation and development and assesses the impact evaluation data and student outcomes of the PH MOOC. Methods: The PH MOOC pilot was launched in Brazilian Portuguese, using the TelessaúdeRS-UFRGS platform on 4/27/2020 and concluded on 7/19/2020 with a total load of 80 h. It was composed of 8 content modules, pre and post-test, 10 topics in a forum discussion, and an optional action plan. This study analyzes the course database, profile of participants, answers to questionnaires, forum interaction, and action plans submitted. Results: Two thousand seven hundred seventy-seven participants enrolled in the course, of which 1,237 (44.54%) gave informed consent for this study. Of the 1,237 participants who agreed to participate in the research, 614 (49.8%) completed the course, and 569 (92.67%) were accredited by TelessaúdeRS-UFRGS. The majority of the participants were concerned with climate change, trained in the health area, and worked in primary health care in places that lacked ongoing sustainability programs. Two hundred forty-one action plans were submitted, major topics identified were food and nutrition, infectious diseases, and garbage and recycling. Discussion: The use of the PH lens and open perspective of the course centered the need to communicate planetary health topics to individuals. The local plans reflected the motto of “think global and act local.” Brazil presents a context of an unprecedented social, political, and environmental crisis, with massive deforestation, extensive fires, and biomass burning altering the biomes, on top of an ongoing necropolitical infodemic and COVID-19 pandemic. In the face of these multiple challenges, this MOOC offers a timely resource for health professionals and communities, encouraging them to address planetary challenges as fundamental health determinants.